2016
DOI: 10.1094/pdis-03-16-0370-re
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Oxathiapiprolin in Bell Pepper Plants and Systemic Protection of Plants Against Phytophthora Blight

Abstract: Production of bell pepper is seriously affected by Phytophthora capsici, the causal agent of Phytophthora blight. Limited approaches are available for effective management of the disease. Oxathiapiprolin is a fungicide recently registered in the United States that suppressed P. capsici and reduced Phytophthora blight on bell pepper significantly in our previous studies. It is unknown whether oxathiapiprolin translocates in bell pepper plants systemically after application. Experiments were conducted to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…1003318-67-9, C 24 H 22 F 5 N 5 O 2 S, structure in Figure 1), first discovered and developed by Dupont in July 2012 and listed in 2016, is the first piperidinyl thiazole isoxazoline fungicide exhibiting a moderate to high persistence, and it inhibits the oxysterol binding protein (OSBP) to kill fungi [7,8]. It offers growers new options for controlling black shank, late blight, and downy mildew in potatoes, grapes, citrus, tobacco, and vegetable crops [9][10][11][12][13][14][15][16]. Currently, oxathiapiprolin has been registered for use on tomatoes, cucumbers, peppers, potatoes, grapes, and other crops in China [6], and its typical metabolites are IN-E8S72, IN-WR791, and IN-SXS67 [17].…”
Section: Introductionmentioning
confidence: 99%
“…1003318-67-9, C 24 H 22 F 5 N 5 O 2 S, structure in Figure 1), first discovered and developed by Dupont in July 2012 and listed in 2016, is the first piperidinyl thiazole isoxazoline fungicide exhibiting a moderate to high persistence, and it inhibits the oxysterol binding protein (OSBP) to kill fungi [7,8]. It offers growers new options for controlling black shank, late blight, and downy mildew in potatoes, grapes, citrus, tobacco, and vegetable crops [9][10][11][12][13][14][15][16]. Currently, oxathiapiprolin has been registered for use on tomatoes, cucumbers, peppers, potatoes, grapes, and other crops in China [6], and its typical metabolites are IN-E8S72, IN-WR791, and IN-SXS67 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Others showed efficacy of soil drenches with oxathiapiprolin against black shank in tobacco [ 12 ], Phytophthora root rot in citrus [ 14 ] and Phytophthora blight in bell pepper [ 13 ]. No soil drench tests with the above fungicides were reported for potato.…”
Section: Discussionmentioning
confidence: 99%
“…Protection of the foliage was already detected at 1 day after root treatment, suggesting a rapid acropetal translocation of the compounds from the root. Qu et al [ 13 ] reported that when oxathiapiprolin was applied to the roots of bell pepper plants grown in hydroculture, the compound was detected in the second true leaf within 8 h and in the top new leaf 48 h after application to the root. In potted plants, translocation to the top new leaf was slower, within 3 days after application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be applied via foliar sprays, soil applications (e.g. in-furrow) or soil drenches and it is efficiently translocated throughout plant tissues in a variety of horticultural species (Cohen 2015(Cohen , 2020Qu et al 2016b), including perennial tree crops (Gray et al 2020). In addition, oxathiapiprolin has low phytotoxic effects in host tissue.…”
Section: Introductionmentioning
confidence: 99%